Fate of CO₂ in tallgrass prairie watershed underlain by merokarst bedrock, Konza Prairie, Kansas, USA - Andrews, Katherine R. (Kansas State University, 2021)
Groundwater is a major sink for carbon dioxide (CO₂) generated in soils. Along groundwater flow, mineral weathering and microbial reactions consume some portion of the CO₂, limiting the amount lost to the atmosphere where the groundwater discharges. To better understand the fate of CO₂ in carbonate terrains, we examined variation in groundwater and surface water chemistry in shallow carbonate aquifers at Konza Prairie, in northeast Kansas, USA. We collected 29 water samples from 11 wells and two stream sites during baseflow conditions in Konza watershed N04d during fall, 2020. The wells are completed in two thin (< 1 m) Permian carbonate units interbedded with mudstones (merokarst). We chemically characterized the water chemistry using standard techniques and used speciation calculations to assess CO₂ concentrations. We also analyzed water isotopes in all samples to assess recharge timing and concentrations of chlorofluorocarbons (CFC-12, CFC-11, CFC-113) and sulfur hexafluoride (SF₆) in nine samples to better understand groundwater residence time. Water isotope compositions we measured are consistent with precipitation during May each year and apparent groundwater ages range from 2.33 to 35 years for SF₆ and from 33.67 to 49 years for CFC-12. Despite the relatively short residence times, the groundwater appears to have been largely in equilibrium with the carbonate bedrock. Calcite was only slightly undersaturated in most groundwater samples (avg. log Q/K = -0.05) and concentrations of CO₂ and weathering products did not vary significantly with groundwater age. Using a simple inverse-modeling calculation, we estimate that carbonate weathering consumed roughly 60% of the CO₂ present during recharge. Compared to the groundwater samples, calcite was generally further from equilibrium in the stream water. Saturation index values ranged up to 1.54 on warm sampling days (water T > 20°C) and as low as -0.39 on cold days (T near or below 10°C), reflecting the temperature dependence of CO₂ outgassing and its impact on the pH of stream water. Taken together, our results illustrate the rapid nature of carbonate weathering and the strong dependence of CO₂ outgassing on stream water temperature.
Keywords: CO₂; Karst; CarbonatesGroundwater